China's life satisfaction, 1990 - 2010 - Richard A. Easterlin; Robson Morgan; Malgorzata Switek; Fei Wang (Institute for the Study of Labor (IZA), 2013)
Despite its unprecedented growth in output per capita in the last two decades, China has essentially followed the life satisfaction trajectory of the central and eastern European transition countries - a U-shaped swing and a nil or declining trend. There is no evidence of an increase in life satisfaction of the magnitude that might have been expected to result from the fourfold improvement in the level of per capita consumption that has occurred. As in the European countries, in China the trend and U-shaped pattern appear to be related to a pronounced rise in unemployment followed by a mild decline, and an accompanying dissolution of the social safety net along with growing income inequality. The burden of worsening life satisfaction in China has fallen chiefly on the lowest socioeconomic groups. An initially highly egalitarian distribution of life satisfaction has been replaced by an increasingly unequal one, with decreasing life satisfaction in persons in the bottom third of the income distribution and increasing life satisfaction in those in the top third.
Keywords: I31; I38; D60; O53; P36; 330; economic growth; Easterlin Paradox; happiness; life satisfaction; subjective well-being; transition countries; China